Care challenges of diabetes mellitus acute complications in adult emergency services - Daiani Moraes Oliveira; Soraia Dornelles Schoeller; Karina Almeida Hammerschmidt; Denise Maria Guerreiro Vieira da Silva; Cecília Arruda (Universidade Federal de Goias, 2016)
Diabetes mellitus imposes multiple challenges to affected people, their families and to the health system. The objective was to analyze strengths and fragilities of nursing attention for diabetes mellitus acute complications in an adult emergency service. A qualitative, descriptive-exploratory study, conducted between May and July of 2013, through semi-structured interviews with 18 nursing professionals at hospital at South of Brazil. To organize and analyze data, theme categories were given: structuring health services and, working teams; each one with their strengths and fragilities. It was noted that the challenge to qualify attention for diabetes patients goes beyond structuring the health attention network and establishing adequate assistencial routines for each institution. They are connected to technical knowledge of the professional team, development of communication abilities, and awareness about the importance of self-care and adherence to treatment.